Vitamin D Deficiency Prevalence And Its Association with Bacterial Load Sputum in Newly Diagnosed TB Patients (Majalah Kedokteran Bandung, 2020)
Vitamin D plays a role in innate and adaptive immune functions, and its deficiency has become a risk factor for TB infection. This study aimed to describe the prevalence of vitamin D deficiency in newly diagnosed TB patients and to examine the relationship between vitamin D levels and sputum smear positivity that reflects bacterial load. This is a cross-sectional study conducted at several primary health care facilities in Medan and Deli Serdang from November 2015 to June 2016. As many as 86 subjects adult TB patients with positive smear sputum who had not received therapy or had at most 1 week on therapy were recruited. Sputum examination were interpreted using IUATLD (International Union Against Tuberculosis and Lung Disease) grading scale. Serum 25 (OH) vitamin D level was estimated using enzyme-linked immunosorbent assay (ELISA) and interpreted as deficiency (
Keywords: bacterial load; pulmonary tuberculosis; vitamin D deficiency